2003
DOI: 10.5194/hess-7-722-2003
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient water quality of the Wye catchment, UK: exploring patterns and fluxes using the Environment Agency data archives

Abstract: Water quality data, collected by the Environment Agency in England and Wales over 10 years (1991 2000) were used to examine the spatial distribution of nutrient pollution risk and for assessing broad-scale spatial and temporal variability in nutrient fluxes across the Wye catchment. Nutrient water quality across the upper and middle Wye catchment, and along the main River Wye, is generally very good. However, the main areas of concern lie in the small tributaries in the south and east of the catchment, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 18 publications
2
43
0
Order By: Relevance
“…Such data complement long-standing environmental monitoring as part of the management of both riverine and lacustrine water bodies by regulatory agencies such as the Environment Agency of England and Wales, and the Scottish Environmental Protection Agency (Robson and Neal, 1997a,b;Jarvie et al, 2003a). Both types of data are vital for addressing issues such as sewage effluent and agricultural runoff of pollutants to water courses and their environmental consequences and making the information freely available for research and management purposes is of critical importance (Tromp-van Meerfield et al, 2008;Schofield et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Such data complement long-standing environmental monitoring as part of the management of both riverine and lacustrine water bodies by regulatory agencies such as the Environment Agency of England and Wales, and the Scottish Environmental Protection Agency (Robson and Neal, 1997a,b;Jarvie et al, 2003a). Both types of data are vital for addressing issues such as sewage effluent and agricultural runoff of pollutants to water courses and their environmental consequences and making the information freely available for research and management purposes is of critical importance (Tromp-van Meerfield et al, 2008;Schofield et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…An investigation of the quality of the data revealed that on several occasions TRP concentrations were much higher than T P concentrations. This is likely to be due to analytical problems (see Neal et al, 2000;Jarvie et al, 2003). The relative uncertainty of the observed TRP concentration was about 20%.…”
Section: Observed Loads At Costessey Millmentioning
confidence: 99%
“…The rural catchment (4136 km 2 ) and invertebrate communities of the River Wye have been comprehensively described elsewhere (Edwards and Brooker, 1982;Ormerod and Edwards, 1987;Jarvie et al, 2003;Clews and Ormerod, 2009). In the middle and upper reaches, pastoral agriculture is the dominant land-use, with rough grazing and plantation forestry also present.…”
Section: Site Description and Managementmentioning
confidence: 99%